A New Macrocyclic Diterpene Derived from the Seed of Euphorbia lathyris - Li, Shu-Hua; Cheng, Ying; Hu, Jian-Ping (Asian Journal of Chemistry, 2012)
A new macrocyclic diterpene, along with two known macrocyclic diterpenes, was isolated from the seed of Euphorbia lathyris L. The new macrocyclic diterpene, designated as Euphorbia lathyris A (1), the structure was elucidated on the basis of the spectroscopic data interpretation. In addition, two known macrocyclic diterpenes were also isolated and identified as Euphorbia Factor L1 (2) and Euphorbia Factor L2 (3).